Characterising collective tenure security in pastoral systems in Burkina Faso - Sawadogo, Issa; Illy, Elie; Ly, Boubacar; Diallo, Safiatou; Badini, Ismael; Magnini, Jufferin; Nassef, Magda (SPARC, 2024)
This study focused on ‘perceived’ tenure security, i.e. how secure people feel. This recognised that perceived tenure security can be a function of formal (legal) recognition of access and use rights, as well as an individual or group’s experiences. Findings at community level include: a description of the pastoral community and collective land under study; the de facto tenure system at community level; the characteristics of the local tenure system, perceived tenure security and factors that affect community perceptions; and differences for individuals vis-à-vis the collective.